Acute appendicitis coexisting with acute pyelonephritis causing diagnostic dilemma: a case report - Ozkan, Burak; Ustun, Cemal; Coskuner, Enis Rauf (SPRINGER, 2021)
Background Acute appendicitis and acute pyelonephritis are the most common diseases admitted to emergency departments. Both conditions have common symptoms such as flank pain, abdominal pain, and fever. Patients' history, physical examination, laboratory evaluation, and imaging methods are used to differentiate these two conditions. Diverticulitis, colitis, gynecological pathologies, and ureteral stones that mimic acute appendicitis should be kept in mind as differential diagnoses. Cases of pyelonephritis mimicking acute appendicitis have been reported in the literature, but there has not been a reported case in which acute appendicitis occurs during management of acute pyelonephritis. In this article, a case report which can cause such a diagnostic dilemma has been presented. Case presentation A 42-year-old female patient presented with clinical features suggestive of acute appendicitis that developed after a diagnosis of acute pyelonephritis. She underwent laparoscopic appendectomy on account of acute appendicitis during medical treatment for acute pyelonephritis. Physical examination showed only right costovertebral tenderness without any rebound tenderness at McBurney's point at the first admission, but during treatment rebound tenderness at McBurney's point was also detected. The Alvarado score of the patient was 5 at the first admission and 7 when acute appendicitis was diagnosed. The patient fully recovered and was discharged after both diseases were completely treated. Conclusions As seen in this case, it should be remembered that both diseases can be seen together which causes a diagnostic dilemma. If clinical or biochemical progression is detected in a patient under treatment, imaging methods should be repeated and additional ones with higher resolutions should be used.
Keywords: Acute pyelonephritis; Acute appendicitis; Medical treatment; Appendectomy; Case report